ІМУНОФЕНОТИП ЛЕЙКЕМІЧНИХ КЛІТИН У ХВОРИХ НА ХРОНІЧНУ ЛІМФОЦИТАРНУ ЛЕЙКЕМІЮ З МУТАЦІЯМИ ГЕНІВ NOTCH1 ТА SF3B1 - Golyarnik, N.; Абраменко, І.; Movchan, G.; Martina, Z.; Dyagil, I.; Chumak, A.; Bazyka, D. (PH Akademperiodyka, 2023)
Background. The typical chronic lymphocytic leukemia (CLL) immunophenotype is vital for diagnosis, but the expression of some antigens varies and has prognostic value. There are data that reduced CD20 expression is associated with NOTCH1 and SF3B1 gene mutations. Aim. To determine a high-risk group of CLL patients for prediction of unfavorable NOTCH1 and SF3B1 gene mutations based on immunophenotyping of leukemic cells. Materials and Methods. Flow cytometric and molecular-genetic analysis (mutations of NOTCH1, SF3B1, and TP53 genes using the polymerase chain reaction followed by direct sequencing) was performed in a group of 86 previously untreated CLL patients. Results. The immunophenotype of leukemic cells of all examined patients met the criteria of CLL diagnosis. NOTCH1 gene mutations were found in 21 patients (24.4%), and SF3B1 gene mutations — in 7 patients (8.1%). There were no TP53 gene mutations among the examined patients. A decreased number of CD20+CD5+ cells and a downward trend in the relative index of mean fluorescence intensity (iMFI) of CD20+ cells were found in patients with NOTCH1 and SF3B1 gene mutations. Based on the iMFI level (higher and/or lower than 3.0) and the number of CD20+CD5+ cells among all B-cells (higher and/or lower than 50%), we distinguished CLL cases with low and relatively high levels of CD20 antigen expression. Using ROC analysis and the parameter of low CD20 antigen expression, we could predict the presence of NOTCH1 and SF3B1 gene mutations in 73.3 ± 0.06% of patients (p = 0.001). The risk of NOTCH1 and SF3B1 gene mutations in cases with low CD20 antigen expression was 6.96 (95% CI = 2.53—19.18; p = 0.0001). The revealed regularities were statistically significant for patients in whom the diagnosis was established in all Binet — Rai stages except A0—AI. Conclusion. Our data confirmed a reduced CD20 expression in CLL patients with NOTCH1 and SF3B1 mutations. In addition, an approach was proposed to identify high-risk CLL patients for prediction of such mutations: previously untreated CLL patients at advanced Binet — Rai stages (BII, CIII, CIV) with a reduced number of double-positive CD20+CD5+ cells in peripheral blood and/or low iMFI of CD20+ cells.